Nb3Sn superconducting radiofrequency cavities: fabrication, results, properties, and prospects. (23rd January 2017) - Posen, S; Hall, D L
Abstract: A microns-thick film of Nb3 Sn on the inner surface of a superconducting radiofrequency (SRF) cavity has been demonstrated to substantially improve cryogenic efficiency compared to the standard niobium material, and its predicted superheating field is approximately twice as high. We review in detail the advantages of Nb3 Sn coatings for SRF cavities. We describe the vapor diffusion process used to fabricate this material in the most successful experiments, and we compare the differences in the process used at different labs. We overview results of Nb3 Sn SRF coatings, including CW and pulsed measurements of cavities as well as microscopic measurements. We discuss special considerations that must be practised when using Nb3 Sn cavities in applications. Finally, we conclude by summarizing the state-of-the-art and describing the outlook for this alternative SRF material.